Social vulnerability and the impact of policy responses to COVID‐19 on disabled people - Mladenov, Teodor; Brennan, Ciara Siobhan (Sociology of Health & Illness, 2021)
In this paper, we propose a conceptual framework for understanding the impact of the policy responses to COVID-19 on disabled people. These responses have overwhelmingly focused on individual vulnerability, which has been used as a justification for removing or restricting rights. This suggests the need to shift the attention towards the social determinants of disabled people's vulnerability. We do this by bringing literature on social vulnerability in disaster risk management or 'disaster studies' in contact with key concepts in disability studies such as the social model of disability, independent living, intersectionality, and biopower. Empirically, we draw on the findings of the global COVID-19 Disability Rights Monitor (www.covid-drm.org), as well as on reports from academic journals, civil society publications, and internet blogs. We put the proposed conceptual framework to work by developing a critical analysis of COVID-19 policies in three interrelated areas-institutional treatment and confinement of disabled people, intersectional harms, and access to health care. Our conclusion links this analysis with strategies to address disabled people's social vulnerability in post-pandemic reconstruction efforts. We make a case for policies that address the social, economic, and environmental conditions that disproportionately expose disabled people to natural disasters and hazards.
https://www.ncbi.nlm.nih.gov/pmc/articles/PMC8652534/
Keywords: approches et analyses; capacitisme; corps; covid-19; discipline; intersectionnalité; ressource en ligne; santé; sciences humaines; sociologie; soins de santé; thématiques; vulnérabilité

Gendered care work and environmental injustice: A feminist analysis of educator's emotional labor in disaster recovery - Shtob, Daniel A.; Petrucci, Larissa (Environmental Justice, 2021)
Although environmental justice researchers have long been interested in the connections between disaster recovery, gender, and home- and community-based care, the consequences of the post-disaster performance of emotional labor by workers in care occupations have largely gone unnoticed. To address this gap in the environmental injustice literature, in this exploratory article we employ a feminist analysis of firsthand accounts of elementary educators' professional and personal experiences caring for their students in the Florida Keys after Hurricane Irma. We find that caring labor was increasingly necessary in the post-disaster context, both inside and outside the classroom. Teachers and other care professionals in feminized occupations may, therefore, perform an emotional double duty, supporting their students' emotional needs while also contending—as working- and middle-class individuals—with the personal consequences of disaster. We suggest that these educators may bear an unrecognized and undercompensated disproportionate burden at the intersection of class and occupational status. Because of this, we introduce an underexplored component to the racialized disaster patriarchy and intersectional disaster research: feminized occupational status. Inspired by environmental justice research legacies developed in the wake of earlier Gulf Coast disasters, we draw attention to the contributions of these absolutely essential recovery workers and how they may experience environmental injustice even as they contribute to others' recovery. Our goals are to promote recognition and fair distribution of burdens, encourage research into the contours of environmental justice and care work, and support the development of more just planning, training, and compensation regimes.
Keywords: amériques; approches et analyses; care; discipline; floride; intersectionnalité; patriarcat; régions géographiques; sciences humaines; sociologie; systèmes d'oppression; thématiques; travail; émotions